2013
DOI: 10.1089/ees.2011.0400
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Retention Time as a Suitable Operational Parameter to Remove Both Estrogen and Nutrients in an Anaerobic–Anoxic–Aerobic Activated Sludge System

Abstract: Estrogen in wastewater are responsible for a significant part of the endocrine-disrupting effects observed in the aquatic environment. The effect of sludge retention time (SRT) on the removal and fate of 17b-estradiol (E2) and 17a-ethinylestradiol (EE2) in an anaerobic-anoxic-oxic activated sludge system designed for nutrient removal was investigated by laboratory-scale experiments using synthetic wastewater. With a hydraulic retention time of 8 h, when SRT ranged 10-25 days, E2 was almost completely removed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The highest biotransformation removal rate was found for TCS and BPA in reactors operating at higher SRTs, whereas a lower biotransformation removal rate of 58% was found for EE2 in the reactor operating at an SRT of 5 d and HRT of 4 h. The mass flux observations in excess sludge showed that the removal of selected microconstituents, as a result of the sludge disposal, was minimal in all experimental runs. Similar results were observed in previous studies for BPA and TCS (Stasinakis et al, 2010;Zhao et al, 2008), and for EE2 (Joss et al, 2004;Li et al, 2011;Muller et al, 2008;Zeng et al, 2013). In contrast, some researchers found higher removal of TCS in full-scale activated sludge systems because of sorption on the suspended solids (Heidler and Halden, 2007;Nakada et al, 2010).…”
Section: Resultssupporting
confidence: 89%
“…The highest biotransformation removal rate was found for TCS and BPA in reactors operating at higher SRTs, whereas a lower biotransformation removal rate of 58% was found for EE2 in the reactor operating at an SRT of 5 d and HRT of 4 h. The mass flux observations in excess sludge showed that the removal of selected microconstituents, as a result of the sludge disposal, was minimal in all experimental runs. Similar results were observed in previous studies for BPA and TCS (Stasinakis et al, 2010;Zhao et al, 2008), and for EE2 (Joss et al, 2004;Li et al, 2011;Muller et al, 2008;Zeng et al, 2013). In contrast, some researchers found higher removal of TCS in full-scale activated sludge systems because of sorption on the suspended solids (Heidler and Halden, 2007;Nakada et al, 2010).…”
Section: Resultssupporting
confidence: 89%
“…The results confirm that an SRT of 25 d (as applied from Day 181 to 305) was adequate to support proliferation of both heterotrophic and slow-growing nitrifying microorganisms that sustain high organics removal, and particularly nitrification. Previous studies also noted that WWTPs operating at SRTs longer than 10 d can induce high removal efficiencies of bulk organics and nutrients (Zeng et al, 2013). It is also interesting to note that more than 90% phosphate removal (Supplementary Data Figure S5) was achieved during operation at an SRT of 25 d and an IR ratio of 3 although the system was not specifically designed for phosphorous removal (i.e., a strictly anaerobic reactor was not used).…”
Section: Bulk Organics and Nutrient Removalmentioning
confidence: 81%
“…Overall, the previous study indicated that shortterm GO exposure could have different effects on microorganisms, i.e., low concentration of GO might have positive impact on nitrogen removal, while high concentration of GO would inhibit the activity of microorganisms. However, GO could adsorb on the sludge [25] and the SRT is longer about 10-25 days [26]. Therefore, GO might accumulate in the sludge have chronic effects on biological treatment systems.…”
Section: Introductionmentioning
confidence: 99%